PENINGKATAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI SISWA KELAS V MELALUI MODEL PROBLEM BASED LEARNING DI SD NEGERI 05 KUBANG PUTIAH KECAMATAN BANUHAMPU KABUPATEN AGAM - Raisa Hanifa; Nur Azmi Alwi (STKIP Subang, 2025)
The background of this study stems from field observations showing that students’ writing skills have not reached optimal results. This is due to the lack of student-centered learning activities, as the teaching process remains teacher-centered, resulting in low student engagement. The purpose of this research is to describe the improvement of students’ descriptive writing skills through the implementation of the Problem-Based Learning (PBL) model in Grade V at SD Negeri 05 Kubang Putiah, Banuhampu District, Agam Regency. This study is a classroom action research (CAR) employing both qualitative and quantitative approaches. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observation, tests, and non-test techniques, focusing on learning outcomes using the PBL model. The research subjects included the students, the classroom teacher as observer, the researcher as practitioner, and 24 Grade V students at SD Negeri 05 Kubang Putiah. The results indicate significant improvements: First, the average score for the teaching module increased from 79.16% (Fair) in Cycle I to 91.66% (Very Good) in Cycle II. Second, the teacher’s performance improved from 85.71% (Good) to 92.85% (Very Good). Third, student participation rose from 80.35% (Good) to 92.85% (Very Good). Fourth, students’ writing skills improved from an average of 79.25 (Fair) to 93.14 (Very Good). Fifth, students’ knowledge scores increased from 65.06% (Poor) to 84.81% (Good). These findings demonstrate that the Problem-Based Learning model effectively enhances students’ descriptive writing skills in Grade V at SD Negeri 05 Kubang Putiah.